Environmental noise reduction configuration: effects on preferences, satisfaction, and speech understanding. - Zakis JA; Hau J; Blamey PJ (International Journal of Audiology, 2009)
The effects of four configurations of an environmental noise reduction (ENR) algorithm on preferences, speech understanding, and satisfaction were investigated. The gain reduction at 0 dB modulation depth was either 10 dB in all channels (ENR StrongFlat) or shaped from 2-10 dB across channels according to a speech importance function (ENR MildSII). This gain reduction was either invariant (ENR Constant) or varied with (ENR Variable) the noise level. Ten hearing-impaired participants blindly compared pairs of configurations in real-world situations and recorded their preferences. Sentence reception thresholds (SRTs) were measured in quiet and noise, and satisfaction was rated with speech in noise. Half of the participants preferred ENR MildSII and half preferred ENR StrongFlat. All preferred ENR Variable to ENR Constant. Overall, the preferred ENR configuration was preferred to ENR off in 90% of responses. No statistically significant effect on SRTs was found, but a clinically significant effect of up to 2 dB could not be ruled out from the available data. ENR significantly improved satisfaction for listening comfort, ease of speech understanding, and sound quality.